Randomized trial for superiority of high field strength intra-operative magnetic resonance imaging guided resection in pituitary surgery. (March 2017) - Tandon, Vivek; Raheja, Amol; Suri, Ashish; Chandra, P. Sarat; Kale, Shashank S.; Kumar, Rajinder; Garg, Ajay; Kalaivani, Mani; Pandey, Ravindra M.; Sharma, Bhawani S.
Highlights: First randomized clinical trial to assess superiority of IOMRI over conventional fluoroscopy in pituitary surgery. Extent of resection was similar in both treatment arms. Endoscopic resection lead to higher remission rates than microscopic resection. Overall 17% patients (8/48) were misdiagnosed as complete resection after post-op MRI was done. IOMRI helped optimize resection rate in 25% (5/20) of patients operated in study arm A. Abstract: Till date there are no randomized trials to suggest the superiority of intra-operative magnetic resonance imaging (IOMRI) guided trans-sphenoidal pituitary resection over two dimensional fluoroscopic (2D-F) guided resections. We conducted this trial to establish the superiority of IOMRI in pituitary surgery. Primary objective was to compare extent of tumor resection between the two study arms. It was a prospective, randomized, outcome assessor and statistician blinded, two arm ( A: IOMRI, n = 25 and B: 2D-F, n = 25 ), parallel group clinical trial. 4 patients from IOMRI group cross-over to 2D-F group and were consequently analyzed in latter group, based on modified intent to treat method. A total of 50 patients were enrolled till completion of trial ( n  = 25 in each study arm). Demographic profile and baseline parameters were comparable among the two arms ( p  > 0.05) except for higher number of endoscopic procedures and experienced neurosurgeons (>10 years) in arm B ( p  = 0.02, 0.002 respectively). Extent of resection was similar in both study arms ( A, 94.9% vs B, 93.6%; p = 0.78 ), despite adjusting for experience of operating surgeon and use of microscope/endoscope for surgical resection . We observed that use of IOMRI helped optimize the extent of resection in 5/20 patients (25%) for pituitary tumor resection in-group A. Present study failed to observe superiorty of IOMRI over conventional 2D-F guided resection in pituitary macroadenoma surgery. By use of this technology, younger surgeons could validate their results intra-operatively and hence could increase EOR without causing any increase in complications.